Seedless and catalyst-free growth of zinc oxide nanostructures on graphene by thermal evaporation [electronic resource] - Nurul Fariha Ahmad, 1990- author; Abdul Manaf Hashim; Universiti Teknologi Malaysia. Institut Teknologi Antarabangsa Malaysia-Jepun (2015)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2015